Palaeointensity of West Greenland Palaeocene basalts: asymmetric intensity around the C27n–C26r transition (Dataset) ... - Riisager, Peter; Abrahamsen, Niels (Magnetics Information Consortium (MagIC), 2010)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Palaeointensity of West Greenland Palaeocene basalts: asymmetric intensity around the C27n–C26r transition ...